Clinical risk prediction for left atrial appendage thrombus among patients with atrial fibrillation. (3rd October 2022) - Segan, L; Nanayakkara, S; Spear, E; Shirwaiker, A; Chieng, D; Sugumar, H; Ling, L H; Prabhu, S; Lee, G; Morton, J; Kalman, J; Voskoboinik, A; et al.
Abstract: Background: Exclusion of left atrial appendage thrombus (LAAT) by transoesophageal echocardiography (TOE) is recommended in patients with inadequate anticoagulation prior to direct cardioversion (DCR) or catheter ablation for atrial fibrillation/flutter (AF/AFL). LAAT risk factors in this population remain poorly defined. Purpose: Determine LAAT predictors in AF/AFL patients undergoing pre-procedural TOE. Methods: We evaluated available clinical and transthoracic echocardiographic (TTE) parameters in AF/AFL patients undergoing TOE between 1999–2022 in our institution in Melbourne, Australia. Regression analysis identified predictors of LAAT, which were applied to a weighted score developed in the derivation cohort (70%) and validated in the remaining 30%. Results: Of 627 patients (age 62±12 years, 27% female, AF 84%, AFL 16%, left ventricular ejection fraction (LVEF) 44±20%), 24% had LAAT and 13.8% dense spontaneous echo contrast precluding DCR. Anticoagulation was NOAC 56.5%, warfarin 32.1% and none in 11.4%. In the LAAT cohort, thrombus resolution occurred in 39% on serial transoesophageal imaging with a median time to resolution of 131 days (IQR 54–398). Diabetes (p=0.004), prior stroke (p=0.009), coronary disease (p=0.015), renal impairment (p<0.001) and CHADS2VASc >2 (73% vs. 55%, p<0.001) were higher in the LAAT cohort. Age (p=0.093), gender (p=0.689), BMI (p=0.828), anticoagulant type (p=0.316) and diabetes (p=0.107) were not univariate predictors, whereas anticoagulation duration (<30 days), creatinine and TTE markers of remodeling (LVEF, LAVI, RVSP and TAPSE) were independent predictors on univariate and multivariate regression; CHADS2VASc was not significant after adjustment (p=0.090). The weighted risk model included continuous (age, creatinine, LVEF, LAVI, TAPSE and RVSP) and categorical (anticoagulation duration) variables with excellent predictive performance: AUC 0.872 (95% CI 0.798–0.946), PPV 91%, NPV 70% and accuracy 80%. Conclusion: A novel LAAT risk model comprising clinical and echocardiographic parameters enhances risk prediction over CHADS2VASc in AF/AFL and may guide the need for pre-procedural TOE imaging. Funding Acknowledgement: Type of funding sources: None.